Assessment of Fasting Plasma Glucose Among Teenagers in Maiduguri Metropolitan Council - Mamza, Y. P.*, Nasirudeen, N. A., Gali, R. M., Mshelia, DS, (Sokoto Journal of Medical Laboratory Science)
This study assessed the fasting plasma glucose among teenagers attending secondary schools in Maiduguri Metropolitan Council. A total of 300 subjects participated in this study which comprises of 150(50%) males and 150(50%) females. Subjects were aged 13-19 years old. Information about socio-demographic were obtained by a questionnaire. Anthropometric measurement of body weight and height were also taken. Their blood pressure was also measured. Fasting plasma glucose (FPG) was estimated using glucose oxidase method. The mean for age, body mass index (BMI), systolic and diastolic blood pressure were 15.75±1.65 years, 21.38±4.84 Kg/M2, 117.73±11.94mmHg, and 72.98±9.51mmHg respectively. The mean FPG concentration was found to be 4.71±0.88mmol/l. The FPG was categorized in to normal, low probability, impaired FPG and diabetes mellitus. The FPG of 283(94.3%) subjects fall within the normal range, 16(5.3%) subjects had an impaired FPG and 1(0.3%) with confirmed diabetes mellitus. This study showed a significant positive correlation between FPG and BMI (r= 0.215; p<0.01), and significant negative correlation between FPG and age (r= - 0.213; p<0.01). In conclusion, our study has shown that 283(94.3%) of the subjects fall within the normal range, 16(5.3%) had an impaired FPG and 1(0.3%) had confirmed diabetes mellitus. Although the percentage of diabetes mellitus among the teenagers is low, there is need for more awareness campaign and possibly routine medical checkup for these teenagers to identify those who are at risk or are diabetics to facilitate effective management to prevent future complications associated with Diabetes.